Modeling of Polymer Structure and Conformations in Polymer Nanocomposites from Atomistic to Mesoscale: A Review. (2nd July 2016) - Karatrantos, Argyrios; Clarke, Nigel; Kröger, Martin
ABSTRACT: Over the past two decades polymer nanocomposites have received tremendous interest from industry and academia due to their advanced properties comparative to polymer blends. Many computational studies have revealed that the macroscopic properties of polymer nanocomposites depend strongly on the microscopic polymer structure and conformations. In this article we review computer simulation studies of the fundamental problem of homopolymers structure and dimensions in nanocomposites containing bare or grafted spherical or rod nanoparticles. Experimentally, there is controversy over whether the addition of nanoparticles in a polymer matrix can perturb the polymer chains.